On the semi-diagnostic computation of climatological circulation in the western tropical Indian Ocean - SHAJI, C.; RAO, A. D.; DUBE, S. K.; BAHULAYAN, N. (MAUSAM, 2000)
The seasonal mean climatological circulation in the Indian Ocean north of 20°S and west of 80°E during the summer and winter has been investigated using a 3-dimensional, fully non-linear, semi-diagnostic circulation model. The model equations include the basic ocean hydrothermodynamic equations of momentum, hydrostatics, continuity, sea surface topography and temperature and salt transport equations. Model is driven with the seasonal mean data on wind stress at the ocean surface and thermohaline forcing at different levels. The circulation in the upper levels of the ocean at 20, 50, 150, 300, 500 and 1000 m depths during the two contrasting seasons has been obtained using the model, and the role of steady, local forcing of wind and internal density field on the dynamical balance of circulation in the western tropical Indian Ocean is explained. The climatological temperature and salinity data used to drive the model is found to be hydrodynamically adjusted with surface wind, flow field and bottom relief during the adaptation stages. Semi-diagnostic technique is found to be very effective for the smoothening of climatic temperature and salinity data and also to obtain the 3-dimensional steady state circulation, which would serve as initial condition in simulation models of circulation.